2014
DOI: 10.1155/2014/716071
|View full text |Cite
|
Sign up to set email alerts
|

Primary Gallbladder Small Lymphocytic Lymphoma as a Rare Postcholecystectomy Finding

Abstract: Introduction. Primary lymphoma of the gallbladder is an extremely rare entity with approximately 50 cases reported so far. In many of these cases the presenting symptoms were mimicking symptomatic gallstone disease and the diagnosis was made postoperatively, especially when the preoperative imaging results were far from suspicious for malignant disease. Patients and Methods. We report a case of primary lymphoma of the gallbladder in an 85-year-old man with gallstone disease, who was admitted for elective chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Primary gallbladder lymphoma (PGL) is rare with approximately 50 cases reported in the literature. 1 PGL commonly presents as cholecystitis. 2 Extranodal marginal zone lymphoma is the common subtype, and it is more common in old age and women.…”
mentioning
confidence: 99%
“…Primary gallbladder lymphoma (PGL) is rare with approximately 50 cases reported in the literature. 1 PGL commonly presents as cholecystitis. 2 Extranodal marginal zone lymphoma is the common subtype, and it is more common in old age and women.…”
mentioning
confidence: 99%
“…When AAC is caused by a mass arising from the gallbladder or extrahepatic duct, the distinction between gallbladder adenocarcinoma and lymphoma is difficult to achieve without histological confirmation, as was the case with our patient. 2,5 On computed tomography, low-grade lymphomas may present as a slight thickening in the gallbladder wall, whereas high-grade lymphomas tend to form a solid mass or irregular thickening in the wall, but this patient did not have a solid mass more indicative of high-grade lymphoma. 14 Because of a low incidence rate, histopathology should only be performed in patients with suspected malignancy because it would not be cost-effective.…”
Section: Discussionmentioning
confidence: 73%
“…3,4 Patients with widespread lymphoproliferative disease with secondary infiltration of the gallbladder is unusual. 5 We present an extremely rare case of AAC due to sporadic adult Burkitt lymphoma.…”
Section: Introductionmentioning
confidence: 96%
“…We also summarized PNHL-GB cases previously described in the literature (Table IV) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). We found that most cases of PNHL-GB are diagnosed incidentally in cholecystectomy specimens (7).…”
Section: Discussionmentioning
confidence: 78%